Conflicts in the XXI Centure. Interview with Professor Johan Galtung (Norway) - Elena Mikhailovna Savicheva (Vestnik RUDN. International Relations, 2016)
Johan Galtung, professor of Peace Studies, was born in 1930 in Oslo, Norway. He is a mathematician, sociologist, political scientist and the founder of the discipline of Peace Studies. He founded the International Peace Research Institute, Oslo (PRIO, 1959), the world's first academic research center focused on Peace Studies, as well as the influential Journal of Peace Research (1964). He has helped to found dozens of other peace centers around the world. He is currently the president of the Galtung-Institute for Peace Theory & Peace Practice. He has mediated in over 150 conflicts between states, nations, religions, civilizations, communities, and persons since 1957. His contributions to peace theory and practice include conceptualization of peace-building, conflict mediation, reconciliation, nonviolence, theory of structural violence, theorizing about negative vs. positive peace, peace education and peace journalism. In his interview, he speaks about today’s conflicts, the sources of cultural violence and the golden rule of mediation. He also touches the problem of regional security in Europe and Asia, development of Peace Studies and the greatest challenges facing the world today.